2012
DOI: 10.1094/mpmi-02-12-0048-r
|View full text |Cite
|
Sign up to set email alerts
|

Development of Viral Vectors Based on Citrus leaf blotch virus to Express Foreign Proteins or Analyze Gene Function in Citrus Plants

Abstract: Viral vectors have been used to express foreign proteins in plants or to silence endogenous genes. This methodology could be appropriate for citrus plants that have long juvenile periods and adult plants that are difficult to transform. We developed viral vectors based on Citrus leaf blotch virus (CLBV) by duplicating a minimum promoter (92 bp) either at the 3' untranslated region (clbv3'pr vector) or at the intergenic region between the movement and coat protein (CP) genes (clbvINpr vector). The duplicated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 55 publications
(70 reference statements)
1
32
0
Order By: Relevance
“…This different behaviour could be due to (i) the slow accumulation and movement of CLBV in the inoculated plants that would allow normal growth during the initial period, before reaching a threshold virus concentration (and FT expression) necessary to induce flowering and (ii) the uneven accumulation and limited virus titre in fully infected plants that would provide reduced amounts of the FT protein in comparison with transgenic plants expressing FT in all their cells. Several observations support the slow accumulation and movement of CLBV: (i) in plants inoculated with a clbvINpr vector expressing the green fluorescent protein ( clbvINpr ‐GFP), CLBV was detected by RT‐PCR only at the end of the first flush (about 1.5 mpi) (Agüero et al ., ), (ii) in plants inoculated with CLBV‐based vectors carrying fragments of the endogenous citrus genes phytoene desaturase or sulphur , the silencing phenotype was rarely observed in the first flush and more usually in the second flush, always being more intense in the second flush, and (iii) the symptoms of chlorotic blotching and stem pitting induced by CLBV in Dweet tangor ( C. tangerina Hort. ex Tan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This different behaviour could be due to (i) the slow accumulation and movement of CLBV in the inoculated plants that would allow normal growth during the initial period, before reaching a threshold virus concentration (and FT expression) necessary to induce flowering and (ii) the uneven accumulation and limited virus titre in fully infected plants that would provide reduced amounts of the FT protein in comparison with transgenic plants expressing FT in all their cells. Several observations support the slow accumulation and movement of CLBV: (i) in plants inoculated with a clbvINpr vector expressing the green fluorescent protein ( clbvINpr ‐GFP), CLBV was detected by RT‐PCR only at the end of the first flush (about 1.5 mpi) (Agüero et al ., ), (ii) in plants inoculated with CLBV‐based vectors carrying fragments of the endogenous citrus genes phytoene desaturase or sulphur , the silencing phenotype was rarely observed in the first flush and more usually in the second flush, always being more intense in the second flush, and (iii) the symptoms of chlorotic blotching and stem pitting induced by CLBV in Dweet tangor ( C. tangerina Hort. ex Tan.…”
Section: Discussionmentioning
confidence: 99%
“…However, clbvINpr‐AtFT was able to induce flowering during the long period studied (almost 5 years). PCR analysis of individual AtFT clones showed that only 8.5% of the clones analysed yielded a DNA band of a size smaller than that expected for the complete gene, confirming that CLBV‐based vectors are highly stable (Agüero et al ., , ). Although some of the clones sequenced showed nucleotide substitutions leading to amino acid changes, none of these changes affected the amino acids essential for the FT function (Hanzawa et al ., ; Ho and Weigel, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the transgenic approach, a viral vector has several advantages, such as self-replication and long-distance movement, allowing the systemic spread of interesting foreign sequences for efficient expression or virus-induced gene silencing (VIGS) in plant [612]. A viral suppressor is a key regulator for counteracting the RNA-silencing defense in plants [1315].…”
Section: Introductionmentioning
confidence: 99%
“…A suitable viral vector, other than a VIGS vector, for rapid gain-of-function studies in infected wild-type or mutant plants is also important; especially when the transgene causes a lethal phenotype in seedlings of the next generation. Many reports have demonstrated that several virus species can express green fluorescent protein ( GFP ) gene for proving of the concept in viral vector development; however, functional study of gene is lacking [6, 23]. …”
Section: Introductionmentioning
confidence: 99%